Efektivitas Copy the Master Berbantuan YouTube dalam Peningkatan Keterampilan Menulis Teks Pidato Siswa Sekolah Menengah Pertama - Safitri, Nurhana; Pratiwi, Wienike Dinar; Suntoko, Suntoko; Mauludani, Seli (Faculty of Languages and Arts, Universitas Negeri Padang, 2025)
Low literacy levels in schools have a significant impact on students' difficulties in expressing ideas through speech writing . This study aims to measure the effectiveness of the YouTube-assisted “Copy the Master” method on speech writing skills. Using a quasi-experimental design with a pretest-posttest pattern, the research involved 60 eighth-grade students divided into experimental and control classes . Data were collected through tests and observations, then analyzed using the N-Gain test and Independent Sample T-test . The results showed that the experimental class achieved an N-Gain value of 57.16 (moderately effective), significantly outperforming the control class, which scored 24.47 (ineffective). Statistical tests confirmed a significant difference with a p-value < 0.01. The novelty of this research lies in the integration of expert modeling with audiovisual media, which helps students fully understand structure and linguistic style . It is concluded that this method serves as an effective alternative for improving writing competence in the digital era.